(untitled) (Brazilian Journal of Health Research, 2023)
Superior vena cava syndrome (SVCS) is uncommon and results from any condition that leads to relevant obstruction of blood flow through the superior vena cava (SVC). Neoplastic origin stands out as the main cause. Malignant obstruction can occur due to direct tumor invasion into the SVC or by external compression, usually of pulmonary origin, which accounts for about 78 - 85% of related neoplasms. We report a case of SVCS mistakenly being treated as angioedema, the crucial role of dermatological evaluation for the correct diagnosis.